PERAN PEMBACA DALAM MENULIS - Rozimela, Yenni (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2007)
This article explores the role of audience in developing oneâ€™s writing. There are three main issues discussed here: 1) Writing English as a foreign language, 2) considering audience in writing, and 3) acting as audience in writing. A brief of the nature of writing in English as a foreign language is intended to provide an understanding difficulties faced by the students in writing. The second issue deals with theories and research findings showing the importance of considering audience in writing. The last part of this article presents an example of how to take audience into consideration as a strategy to help students develop their writing.Â